EFL CLASS FOR IRREGULAR MIGRANTS IN EDUCATIONAL PROGRAM AT RUMAH DETENSI IMIGRASI SEMARANG - M. Risya Islami (Universitas Islam Negeri Walisongo Semarang, 2016)
This research describes an EFL class for irregular migrants in educational program at Rumah Detensi Imigrasi. Irregular migrants are foreigners staying in Indonesia without any legal document or im- migration permission. Rumah Detensi Imigrasi is a temporary shelter for irregular migrants during waiting periods for refugee status from UNHCR to come to a destination country like Australia, New Za- eland etc. EFL class is a class for irregular migrants at Rumah Detensi Imigrasi to learn English especially speaking and writing skills. The teaching learning process of the EFL class uses Grammar trans- lation, Reading and communicative approaches. The materials de- livered are vocabularies, grammar, speaking and writing skills. The class is aimed at providing students with language skills since most of the destinations are English speaking countries.